Early cystic bleb needling revision after glaucoma filtering surgery with toxic keratopathy - S. Yu. Petrov; E. A. Kasparova; A. A. Antonov; T. S. Mitichkina; S. V. Vostrukhin; D. M. Safonova (Oftalʹmologiâ)
Clinical case of high thin-wall cystic limited filtering bleb needling revision in the early post-op period after trabeculectomy with sinusotomy accompanied by toxic keratopathy is presented. Optical coherence tomography (OCT) demonstrated that filtering bleb height was 2700 μm and bleb wall thickness was 70 μm. Bleb needling revision with its lateralwall dissection and subconjunctival injection of dexamethasone, fluorouracil, and ranibizumab near to the bleb site was performed. In 1.5 hours after the procedure, bleb height decreased to 550 μm (by 5 times) while bleb wall thickness increased up to 100 μm. Topical antibacterial, steroid, and non-steroid anti-inflammatory therapy was recommended. The next day IOP level reduced from 11 mm Hg to 4.5 mm Hg. It was accompanied by choroidal effusion that was managed conservatively with cycloplegic agents (drops and injections) for 3 days. On day 6, central corneal edema affecting all layers, Descemet’s membrane folds, and ocular hypertension were revealed. Metabolic therapy resolved corneal edema within 3 days. Re-needling bleb revision decreased IOP level to 6.2 mm Hg. This resulted in transient Descemet’s membrane folds. This paper describes filtering bleb needling revision with its lateral wall dissection and anti-inflammatory, cytostatic, and anti-VEGF agents use to prolong glaucoma filtering surgery effect in excessive scarring. The procedure was accompanied by toxic corneal endothelium decompensation with corneal edema and Descemet’s membrane folds treated with active metabolic therapy.